(untitled) (Revista Peruana de Investigación Educativa, 2023)
This article goes through the work of the School Technical Boards (CTE in its Spanish acronym) during the 2019-2020 school year, through a comparative analysis between the national and state levels of the follow-up strategy implemented by the General Direction of Educational Management Development of the Public Education Department (DGDGE- SEP in its Spanish acronym) and by the Basic Education Direction of Tlaxcala. This study presents the chartered acting references and the decision-making of the sessions before the COVID-19 pandemic and the ones made during the confinement period. The methodology was cross descriptive quantitative to equal their results averages in relation to the organization and development of the School Technical Boards and the School Improvement Plan (PME in its Spanish acronym). The results show better scores for the national level rather than the state ones.in the ordinary sessions work before the pandemic. When closing the schools because of the social distancing the ordinary educational dynamics and priorities fragmented and gave way to an uncertain decision-making in a new role of the school boards.